Technical capacities needed to implement the WHO's primary eye care package for Africa: results of a Delphi process. Issue 3 (19th March 2021) - Aghaji, Ada; Burchett, Helen E D; Mathenge, Wanjiku; Faal, Hannah Bassey; Umeh, Rich; Ezepue, Felix; Isiyaku, Sunday; Kyari, Fatima; Wiafe, Boateng; Foster, Allen; Gilbert, Clare E
Abstract : Objective: The aim of the study was to establish the technical capacities needed to deliver the WHO African Region's primary eye care package in primary healthcare facilities. Design: A two-round Delphi exercise was used to obtain expert consensus on the technical complexity of each component of the package and the technical capacities needed to deliver them using Gericke's framework of technical feasibility. The panel comprised nine eyecare experts in primary eyecare in sub-Saharan Africa. In each round panel members used a 4-point Likert scale to indicate their level of agreement. Consensus was predefined as ≥70% agreement on each statement. For round 1, statements on technical complexity were identified through a literature search of primary eyecare in sub-Saharan Africa from January 1980 to April 2018. Statements for which consensus was achieved were included in round 2, and the technical capacities were agreed. Results: Technical complexity statements were classified into four broad categories: intervention characteristics, delivery characteristics, government capacity requirements and usage characteristics. 34 of the 38 (89%) statements on health promotion and 40 of the 43 (93%) statements on facility case management were considered necessary technical capacities for implementation. Conclusion: This study establishes the technical capacities needed to implement the WHO Africa Office primary eye care package, which may be generalisable to countries in sub-Saharan Africa.